Analysis of the Pentahelix Model in the Implementation of the Free Nutritional Meal Program at Elementary and Middle School Levels in Gorontalo City - Dian Fitriani Karim; Asna Aneta (GEMA PUBLICA, 2026)
ABSTRACTABSTRACTThis research aims to analyse the Pentahelix model in the implementation of a free nutritious meal programme in Gorontalo City, focusing on primary and secondary education in the pursuit of the Golden Generation 2045. The Pentahelix model involves five key elements: government, academia, industry, community, and media, which collaborate to achieve a shared objective of enhancing the nutritional quality of children. Through a collaborative approach, the free nutritious meal programme is expected to reduce malnutrition rates and improve the quality of education and health for future generations. This study employs qualitative methods, including interviews and observations, to gather data from various stakeholders. The findings indicate that collaboration between the government and the community is crucial for the success of this programme. Furthermore, the role of media in disseminating information about the importance of nutrition has proven to be effective. Therefore, recommendations to enhance the participation of all Pentahelix elements are essential for achieving long-term goals in creating a healthy and productive generation.